2021
DOI: 10.1093/jaoacint/qsab013
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Scopoletin from the Roots of Argyreia Speciosa (Linn. F) Sweet Using HPLC Through the Concept of Design of Experiment

Abstract: Background Roots of Argyreia speciosa (Linn. F) Sweet (family: Convolvulaceae) are used in Ayurveda to treat male reproductive and nervous system disorders. Objective Isolation of scopoletin from the roots of Argyreia speciosa, development and validation of an analytical method using HPLC for the quantification of scopoletin from the root powder of Argyreia speciosa. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…11 Furthermore, the other literature review revealed that there are various methods available for the detection and quantification of eugenol alone or along with other constituents using UV-spectroscopy, 12 High-performance liquid chromatography 13 and LC-MS. 14 Likewise, scopoletin was estimated by UV-spectroscopy, 15 HPTLC 16 and High-performance liquid chromatography. 17 Hence, from the literature review it is clear that there is no method reported in pharmacopoeias for simultaneous analysis of eugenol and scopoletin by UV spectroscopy in Avipattikar churna.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, the other literature review revealed that there are various methods available for the detection and quantification of eugenol alone or along with other constituents using UV-spectroscopy, 12 High-performance liquid chromatography 13 and LC-MS. 14 Likewise, scopoletin was estimated by UV-spectroscopy, 15 HPTLC 16 and High-performance liquid chromatography. 17 Hence, from the literature review it is clear that there is no method reported in pharmacopoeias for simultaneous analysis of eugenol and scopoletin by UV spectroscopy in Avipattikar churna.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was conducted using a RP-ODS C8 (250*4.5 mm). From the literature, UV detection and injection volume (20 µl) were optimized by conducting various trials [13][14][15] .…”
Section: Methods Developmentmentioning
confidence: 99%
“…An analytical method for the estimation of scopoletin from Argyreia nervosa using HPLC coupled with UV detector was also reported. [ 11 ] Scopoletin was estimated from commercial herbal drug product containing asiaticoside along with scopoletin using HPLC coupled with UV/FD (fluorescence detector). [ 12 ] Scopoletin was estimated from rat plasma using HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the development of analytical methods to estimate scopoletin from different plant extracts using HPLC coupled with a fluorometric detector, but comprising gradient mobile phase. [11,16,31,32] The fluorescence signal is obtained as a combination of excitation and emission wavelengths, which helps in the selective detection of the compound of interest. Moreover, the fluorescence detector possesses a better signal-to-noise ratio (S/N) as compared to UV detector which makes them more sensitive.…”
mentioning
confidence: 99%